Rifampicin-associated acute renal failure and hemolysis: a rather uncommon but severe complication. (September 2013) - Manika, Katerina; Tasiopoulou, Karmen; Vlogiaris, Leuteris; Lada, Martha; Papaemmanouil, Styliani; Zarogoulidis, Konstaninos; Kioumis, Ioannis
Abstract Rifampicin is a widely used anti-tuberculosis agent. Apart from hepatotoxicity, rifampicin can rarely lead to adverse reactions of immunologic nature such as acute renal failure (ARF). We report the case of 57-year-old previously healthy man under treatment for pulmonary tuberculosis who presented with hemolysis and severe ARF. Rifampicin was discontinued and the patient was treated with fluid repletion, iv furosemide and dialysis therapy. Kidney biopsy revealed acute tubulointerstitial nephritis with no evidence of granulomas. The patient significantly improved and was discharged after 51 days of hospitalization. Clinicians using rifampicin should be aware of this rather uncommon but severe complication.